Session-RPE method for training load monitoring: Validity, ecological usefulness, and influencing factors - Haddad, M.; Stylianides, G.; Djaoui, L.; Dellal, A.; Chamari, K. (Frontiers in Neuroscience, 2017)
Purpose: The aim of this review is to (1) retrieve all data validating the Session-rating of perceived exertion (RPE)-method using various criteria, (2) highlight the rationale of this method and its ecological usefulness, and (3) describe factors that can alter RPE and users of this method should take into consideration.